If t1 = 6, t2 = 4, t3 = 2 and $\displaystyle t_n = (t_{n-3} + t_{n-2}) \cdot t_{n-1} $ Find t7.
Follow Math Help Forum on Facebook and Google+
Originally Posted by casey_k If t1 = 6, t2 = 4, t3 = 2 and $\displaystyle t_n = (t_{n-3} + t_{n-2}) \cdot t_{n-1} $ Find t7. Its a matter of applying the recursive forumula. When $\displaystyle n=4$, you have $\displaystyle t_4=(t_1+t_2)\cdot t_3=(6+4)\cdot 2=24$ When $\displaystyle n=5$, you have $\displaystyle t_5=(t_2+t_3)\cdot t_4=(4+2)\cdot 24=144$ Can you continue on with this process?
View Tag Cloud